Adaptation of Technological Pedagogical Content Knowledge Scale to Turkish - Kaya, Zehra; Kaya, Osman Nafiz; Emre, Irfan (Edam, 2013)
The purpose of this study was to adapt Survey of Pre-service Teachers' Knowledge of Teaching and Technology in order to assess pre-service primary teachers' Technological Pedagogical Content Knowledge (TPACK) to Turkish. 407 pre-service primary teachers (227 female and 180 male) in their final semester in Education Faculties in Turkey participating in this study were selected with criteria sampling which is the method of purposeful sampling. Exploratory and confirmatory factor analyses, including Cronbach's alpha and item-total correlation coefficients, were used for checking the psychometric properties of the adapted scale. Exploratory factor analysis (EFA) identified eight factors accounting for 59.44% of the variance, Cronbach's alpha coefficient was found to be .89 for the overall scale, and item-total correlation coefficients were between .42 and .74. The results obtained from the EFA supported by confirmatory factor analysis showed that there were new four factors based on the subject matter (science, mathematics, social studies and literacy) although four factors were the same as in the original scale. It was concluded that the adapted scale should not be used in academic studies focusing on Turkish pre-service primary teachers' TPACK. The unexpected results of this study were discussed for researchers and program developers in Turkish teacher education.
Teknolojik Pedagojik Alan Bilgisi (TPAB) ölçe?i'nin türkçeye uyarlanmasi{dotless}
Keywords: Technological Pedagogical Content Knowledge; Pre-service Teacher Education; Pre-service Primary Teachers; Turkish Teacher Education